Loss of α-9 Nicotinic Acetylcholine Receptor Subunit Predominantly Results in Impaired Postural Stability Rather Than Gaze Stability - Chang, Hui Ho Vanessa; Morley, Barbara J.; Cullen, Kathleen E. (Frontiers in Cellular Neuroscience, 2022)
The functional role of the mammalian efferent vestibular system (EVS) is not fully understood. One proposal is that the mammalian EVS plays a role in the long-term calibration of central vestibular pathways, for example during development. Here to test this possibility, we studied vestibular function in mice lacking a functional α9 subunit of the nicotinic acetylcholine receptor (nAChR) gene family, which mediates efferent activation of the vestibular periphery. We focused on an α9 (-/-) model with a deletion in exons 1 and 2 (Morley et al., 2017). First, we quantified gaze stability by testing vestibulo-ocular reflex (VOR, 0.5-3Hz) responses of both α9 (-/-) mouse models in dark and light conditions. VOR gains and phases were comparable for both α9 (-/-) mutants and wild-type controls. Second, we confirmed the lack of an effect from the α9 (-/-) mutation on central visuo-motor pathways/eye movement pathways via analyses of the optokinetic reflex (OKR) and quick phases of the VOR. We found no differences between α9 (-/-) mutants and wild-type controls. Third and finally, we investigated postural abilities during instrumented rotarod and balance beam tasks. Head movements were quantified using a 6D microelectromechanical systems (MEMS) module fixed to the mouse’s head. Compared to wild-type controls, we found head movements were strikingly altered in α9 (-/-) mice, most notably in the pitch axis. We confirmed these later results in another α9 (-/-) model, with a deletion in the exon 4 region (Vetter et al., 1999). Overall, we conclude that the absence of the α9 subunit of nAChRs predominately results in an impairment of posture rather than gaze.